FORMATION IN SCHOOLCHILDREN NEEDS FOR KNOWLEDGE - Buryak, V.K. (Pedagogy of Higher and Secondary Education, 1999)
When speaking about the process of acguiring new knowledge by pupils, one has to take into consideration the formation of necessity in this knowledge. Different ways of formatio n the necessity in knowledge are shown in the article on the material of experimental work and the results of this work.